2017
DOI: 10.1080/10942912.2017.1368548
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin profile of strawberry fruit as affected by extraction conditions

Abstract: The purpose of the study was to investigate the effect of extraction conditions to determine anthocyanin compounds in strawberry fruit. Anthocyanin profile of this fruit were determined via high-performance liquid chromatography-electrospray ionization-mass spectrometry. Flow rate of mobile phase, fragmentor potential, injection volume, and column temperature were applied to be optimum values as 0.5 mL min −1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…Anthocyanins are a group of water-soluble flavonoids, which show many biological activities in plants, such as imparting stress resistance, extending fruit life or attracting pollinating insects [38]. Moreover, anthocyanins supplied with food have a beneficial effect on the human body through preventing the accumulation of cholesterol in blood vessel walls, preventing cardiovascular diseases and cancers or by regulating blood sugar concentration [39]. Anthocyanins are dominant pigments in strawberry; thus, they are responsible for the red colour of this fruit.…”
Section: Introductionmentioning
confidence: 99%
“…Anthocyanins are a group of water-soluble flavonoids, which show many biological activities in plants, such as imparting stress resistance, extending fruit life or attracting pollinating insects [38]. Moreover, anthocyanins supplied with food have a beneficial effect on the human body through preventing the accumulation of cholesterol in blood vessel walls, preventing cardiovascular diseases and cancers or by regulating blood sugar concentration [39]. Anthocyanins are dominant pigments in strawberry; thus, they are responsible for the red colour of this fruit.…”
Section: Introductionmentioning
confidence: 99%
“…The anthocyanin effects on CRP observed in this present analysis may be explained by the content of cyanidin 3-O-𝛽-glucoside in the investigated fruits. [90,91] In human endothelial cells, it has been shown that cyanidin 3-O-𝛽-glucoside is able to prevent CD40 induced endothelial activation [92] and downregulate the activation of JNK, IKK, COX-2, and IL-6. [93] The downregulation of JNK and IKK, resulting in a decreased activation of AP-1 and NF-𝜅B, leading to a reduced formation of inflammatory agents, including IL-6 which, among others, activates the expression of CRP in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of total phenolic compounds (TPC) at the end of drying is less than the initial concentration in all cases for solar and oven drying. Thermal degradation of phenolic compounds has been previously reported [45][46][47][48] . Nevertheless, in solar drying, we observe an increase in TPC concentration at last stage of drying, similar to the behavior obtained in TA.…”
Section: Total Phenolic Compoundsmentioning
confidence: 99%